THE EFFECT OF EXPLOSION BOX ON KNOWLEDGE AND COMPLIANCE TEENAGE GIRLS IN CONSUMING IRON TABLET SUPPLEMENT - Firdawati, Firdawati; Hazanah, Sri; Tonapa, Emelia (STIKes Medistra Indonesia, 2025)
Female adolescents are at increased risk for anemia since their iron needs peak between the ages of 14 and 15. Youth iron deficiency can lead to serious health problems, including anemia. One student in a group of nine reported having a hemoglobin (Hb) level of 12, and the other four reported experiencing fatigue, weakness, difficulty focusing in class, and other symptoms of anemia. The purpose of this study is to learn how exposure to the media shown in Exploding Box affects young women's self-control and decision-making when consuming dietary supplements. Method: This study has a pre-experimental design with a single-group pre- and post-test. In this study, we used a completely random sample of participants. Students from grades 10, 12, and 15 at MTs Al- Muhajirin Loa Janan make up the study's sample population. Female students fill kuesioners, and male researchers use lembar observatories to compile the data. SPSS is used for both univariate and bivariate data analysis. Research shows that both before and after receiving the intervention, the media explosion box had a significant impact on knowledge (p0,000) and respondent accuracy (p0,003). What this means is that young women at MTs Al- Muhajirin Loa Janan are more knowledgeable about and more likely to follow guidelines for taking tablet supplements of blood. Conclusions Based on research and analysis, it can be concluded that the media's influence on young women's knowledge of and behavior surrounding tablet consumption of added blood sugar is real. The hope is that this media explosion box will serve as a resource for raising awareness and encouraging action among young women to prevent anemia.